Shop manual for automotive engine performance - Pickerill, Ken (Today's technician, 2006)
This comprehensive training/education package focuses on the major engine systems affecting engine performance and drivability. Today's Technician: Automotive Engine Performance, 4th Edition includes thoroughly updated content on ignition systems, intake and exhaust systems, fuels and emission controls and related electronics, in two comprehensive manuals. With a sharp focus on current technologies and the inclusion of outstanding learning features, this new edition provides an excellent classroom resource for students preparing to become future technicians.